Volume 3: Coal, Biomass and Alternative Fuels; Combustion and Fuels; Oil and Gas Applications; Cycle Innovations 1996
DOI: 10.1115/96-gt-130
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Combustion of Natural Gas Over Supported Platinum: Flow Reactor Experiments and Detailed Numerical Modeling

Abstract: The use of a noble-metal combustion catalyst such as platinum or palladium in a natural-gas fired turbine can lower NOx (nitrogen oxides, consisting of both NO and NO2) emissions for two reasons. First, most of the combustion occurs on the catalyst surface; surface production of NOx is low or nonexistent. Second, the catalyst permits low temperature combustion below the traditional lean limit, thus inhibiting NOx formation routes in the gas phase. Due to the complexity of the catalytic combustion process, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…A review of the literature (Bond et al, 1996;Chou et al, 2000) reveals that the majority of existing models are limited to modeling heterogeneous reactions within a single channel of a monolith for combustion of methane. Although such models are important in interpretation of experimental data, their usefulness for overall design and development is limited.…”
Section: Catalytic Combustormentioning
confidence: 99%
“…A review of the literature (Bond et al, 1996;Chou et al, 2000) reveals that the majority of existing models are limited to modeling heterogeneous reactions within a single channel of a monolith for combustion of methane. Although such models are important in interpretation of experimental data, their usefulness for overall design and development is limited.…”
Section: Catalytic Combustormentioning
confidence: 99%
“…A review of the literature [Bond et al, 1996], [Chou et al, 2000] revealed that the majority of existing models were limited to modeling heterogeneous reactions within a single channel of a monolith for combustion of methane. Figure 1.3.54 provides a schematic showing the processes occurring in a single monolith channel.…”
Section: Model Descriptionmentioning
confidence: 99%